Keefektifan Metode Proteksi Data dalam Mengatasi Ancaman Cybersecurity - Arfan Dwi Madya; Bagas Djoko Haryanto; Devi Putri Ningsih; Fried Sinlae (Indonesian Journal of Education And Computer Science, 2023)
Information security has become a primary concern in the current digital era, where the threat of cyber attacks is on the rise. This article discusses the significant growth of internet users and its impact on the increasing incidence of cyber attacks, with a focus on the situation in Indonesia. Data indicates a drastic surge in cyber attacks in Indonesia, reaching approximately 190 million attempts in 2020. Recognizing the importance of a national cyber security strategy, this research aims to evaluate the effectiveness of data protection methods in addressing cybersecurity threats. The research methodology employs a qualitative descriptive approach to explore and understand the effectiveness of data protection methods. Data analysis is conducted holistically to comprehend the context and dynamics influencing the success of data protection methods in facing cybersecurity threats. The research findings emphasize the crucial role of cyber security in safeguarding data, privacy, and the smooth operation of services. Cyber threats encompass various types, including physical, logical, and operational threats. Human factors also pose a serious threat, including user errors and social engineering techniques. Data protection is identified as a key strategy in tackling cybersecurity threats. Measures such as malware detection, defense against DoS and phishing attacks, database security, data encryption, monitoring and response to attacks, as well as education and training, are highlighted as primary focuses for the banking sector